Uncovering the Emerging Prospects of Lipid-based Nanoparticulate Vehicles in Lung Cancer Management: A Recent Perspective - Gupta, Dhruv Sanjay; Suares, Divya (Pharmaceutical Nanotechnology, 2025)
Lung cancer, a leading cause of cancer-related deaths globally, is gaining research interest more than ever before. Owing to the burden of pathogenesis on the quality of life of patients and subsequently the healthcare system, research efforts focus on its management and amelioration. In an effort to improve bioavailability, enhance stability, minimize adverse effects and reduce the incidence of resistance, nanotechnological platforms have been harnessed for drug delivery and improving treatment outcomes. Lipid nanoparticles, in particular, offer an interesting clinical opportunity with respect to the delivery of a variety of agents. These include synthetic chemotherapeutic agents, immunotherapeutic molecules, as well as phytoconstituents with promising anticancer benefits. In addition to this, these systems are being studied for their usage in conjunction with other treatment strategies. However, their applications remain limited owing to a number of challenges, chiefly clinical translation. There is a need to address the scalability of such technologies, in order to improve accessibility. The authors aim to offer a comprehensive understanding of the evolution of lipid nanoparticles and their application in lung cancer, the interplay of disease pathways and their mechanism of action and the potential for delivery of a variety of agents. Additionally, a discussion with respect to results from preclinical studies has also been provided. The authors have also provided a well-rounded insight into the limitations and future perspectives. While the possibilities are endless, there is a need to undertake focused research to expedite clinical translation and offer avenues for wider applications in disease management.
Keywords: nanotherapeutics